Автоматизована система керування накопичувальними бункерами - Ковалевський, В. О.; Лисенко, Володимир Валерійович; Точковий, Д. С. (НТУ "ХПІ", 2010)
В работе рассмотрены вопросы построения автоматической системы управления накопительными бункерами. Представлено техническое решение поставленной задачи. Описан специализированный протокол обмена информации. Составлены расчетные формулы для объемного учета продукции.

We have considered questions of automatic system construction of gathering bins. We have presented the technical solution of assigned task. Also we have created the specialized communication protocol. We have made calculation formulas for volume audit production.
Keywords: мікропроцесорні контролери керування; рушально-війкове відділення; контролер вищого рівня; КВР; МКК; automatic system; specialized communication protocol